Report of the Committee on the affairs of the tribe of the Narragansett Indians (1839), including the "Public regulations of the Indian tribe" (1792)
December 17, 1792 regulations regarding the Narragansett Tribe, as well as those subsequently passed. The regulations were referenced in the second document, a report of the Committee on January 3, 1839 to review various Narragansett complaints. The issues included trespass by whites, rights of membership, marriage outside the tribe, the state of morals, and the necessity of laws preventing suits for debts from liquors.